2015
DOI: 10.1253/circj.cj-15-0412
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Arginine-to-Asymmetric Dimethylarginine Ratio Associated With Blood Pressure Abnormalities in Children With Early Chronic Kidney Disease

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp (NO), a vasodilator, regulates endothelial function and blood pressure (BP). Our previous review indicated emerging evidence supporting that a deficiency of NO links endothelial dysfunction to CVD in pediatric CKD. 3 Because asymmetric dimethylarginine (ADMA) is an analog of L-arginine (ARG), the substrate for NO synthase (NOS), the ARG-to-ADMA ratio (AAR) represents NO bioavailability and maintains NO homeostasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
(22 reference statements)
3
17
0
Order By: Relevance
“…This discrepancy may be due to the fact that only small subgroup of our subjects showed mild to moderate impairment of renal function and we excluded patients with CKD stages 4 and 5. Similarly to our results, no difference was found in terms of ADMA level between pediatric patients with normal kidney function and CKD stages 2 and 3 [16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This discrepancy may be due to the fact that only small subgroup of our subjects showed mild to moderate impairment of renal function and we excluded patients with CKD stages 4 and 5. Similarly to our results, no difference was found in terms of ADMA level between pediatric patients with normal kidney function and CKD stages 2 and 3 [16].…”
Section: Discussionsupporting
confidence: 90%
“…Although ADMA was significantly and independently associated with cIMT in a group of 405 8-year-old Australian children [39], this relation was not confirmed in high-risk patients. ADMA level did not correlate with cIMT in pediatric patients with primary hypertension [14], with cIMT, PWV, and ambulatory arterial stiffness index (AASI) in children with CKD stages 1-3 [16], with cIMT in children with CKD stages 2-5 [17], or with cIMT, PWV, and AIx75HR in children with juvenile idiopathic arthritis [15].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There is plenty of evidence for increasing levels of OS markers with deteriorating renal function, beginning from early CKD stages [11] in both adults and children. Like in adults, data from children and young adults with CKD show increasing concentrations of OS markers such as mitochondrial superoxide and oxidized LDL [90][91][92], homocysteine [93], as well as a deficiency of SOD and GSH [91,92] together with disease progression. Also, several uremic toxins, associated with increased OS in CKD, increase with worsening renal function, such as the retention solute IS [94], F 2 -isoprostanes, MDA, and ADMA [95,96].…”
Section: Polyphenols-flavonoidsmentioning
confidence: 99%
“…On the other hand, in a prospective study the progression of blood pressure on normotensive population over 2-years period Wang et al found that homocysteine is related to hypertension incidence at high levels, and may also increase the risk of hypertension at low levels [142]. Children with early CKD showed blood pressure abnormalities, mostly having a positive correlation with high homocysteine levels along with other factors, in a cross-sectional study [143]. Nevertheless, none of these studies provided strong evidences that the homocysteine causes human hypertension [137, 144].…”
Section: Involvement Of Thiol Homocysteine and H2s In Renovascularmentioning
confidence: 99%